Because of Winn-Dixie - Wang, Wayne, 1949-; Daniels, Jeff, 1955-; Tyson, Cicely; Matthews, Dave, 1967-; Saint, Eva Marie, 1924-; Robb, Annasophia, 1993-; Lindenlaub, Karl Walter; Portman, Rachel; DiCamillo, Kate.; Twentieth Century Fox Home Entertainment, Inc. ([Beverly Hills, Calif.] : 20th Century Fox Home Entertainment, 2005)
A young girl's life is changed by a scruffy, fun-loving pooch she names Winn-Dixie. The special bond between them works magic on her reserved dad and the eccentric townspeople they meet during one unforgettable summer.
Based on the novel by Kate DiCamillo.
"Exclusive Target limited edition"--Container.
Special features: full-length audio commentary by Jeff Daniels and Trevor Albert; scene-specific commentary by Anna Sophia Robb; behind-the-scenes featurette; gag reel; dog training featurette.
Director of photography, Karl Walter Lindenlaub ; editor, Deirdre Slevin ; music, Rachel Portman ; costume designer, Hope Hanafin ; production designer, Donald Graham Burt.
Jeff Daniels, Cicely Tyson, Dave Matthews, Eva Marie Saint, AnnaSophia Robb, Elle Fanning, Courtney Jines, Nick Price, Luke Benward, Marca Price.
DVD, region 1, full screen (1.33:1) or widescreen (1.85:1) presentations; Dolby Digital 5.1, Dolby surround.
Keywords: Dogs -- Juvenile drama; City and town life -- Juvenile drama; Friendship -- Juvenile drama; Dogs -- Drama; Friendship -- Drama; Perros -- Teatro juvenil; Vida urbana -- Teatro juvenil; Amistad -- Teatro juvenil; Feature films; Children's films; Video recordings for the hearing impaired